ChemInform Abstract: Efficient Diels—Alder Reaction of 1, 2‐Benzoquinones with Arynes and Its Utility in One‐Pot Reactions. Issue 19 (18th April 2013) - Kaicharla, Trinadh; Bhojgude, Sachin Suresh; Biju, Akkattu T.
Abstract The arynes react with 1, 2‐benzoquinones to give dioxobenzobicyclooctadienes.